Masculinity and Nationhood, 1830-1910 - Hoegaerts, J. author. aut Link
XI, 242 p.
Keywords: A history of what it meant to be a man, and a citizen of an emerging nation throughout the nineteenth century. This book not only relates how Belgians were taught how to move and fight, but also how they spoke and sang to express masculinity and patriotism.